Research on the factors contributing to flash floods in the Northern mountainous region of Vietnam: criteria, weights, and evaluation indexes - Pham, Huong Giang; Kieu, Quoc Lap (Bulletin of Geography. Physical Geography Series, 2025)
Flash floods are one of the most severe natural disasters, particularly in the northern mountainous regions of Vietnam, where steep terrain and dense river and stream networks are prevalent. These flash floods cause significant loss of life and property, threatening the sustainable development of these areas. However, assessing and forecasting flash flood risks remains challenging due to the lack of specific scientific analysis methods. This study aims to systematically analyze both natural and anthropogenic factors contributing to flash flood risks and to develop a comprehensive, multi-criterion index system for assessing flash flood risk levels in the mountainous river basins of Northern Vietnam. By employing multi-criterion evaluation (MCE) and the Analytic Hierarchy Process (AHP), the study seeks to construct a scientifically robust framework for flash flood risk assessment tailored to the unique geographic and climatic conditions of the region. The study also developed a risk classification map for flash floods in five representative river basins, with areas of very high risk accounting for 20.06% of the study area. The research outcomes, including a risk classification map for representative river basins, are intended to enhance disaster risk management and sustainable development practices in the area.